A relação entre o pensamento de maximização da utilização de recursos e produção puxada: um estudo de caso em profundidade - Linares, João Marcos (2024)
The Brazilian graphics sector is strategic and important, enabling the dissemination of information and improvement in Brazilian education. However, there is a lack of scientific research regarding the methodology and philosophy of Lean Manufacturing. The objective of this work is to evaluate the relationship between the thinking of maximizing the use of resources, which contrasts with the philosophy of lean thinking. From a conceptual and theoretical point of view, a systematic bibliographic review was carried out that presented the difficulties and what approaches there are in the literature regarding the implementation of pull production in environments with a high variety of products and high seasonality of demand. From an empirical point of view, an in-depth case study was carried out in a company in the Brazilian graphics sector to understand the reasons and difficulties that decision-making leaders have in changing a mentality focused on efficiency to a mentality focused on reduction. of waste, being the main problematization in which this dissertation seeks to discover. To answer the questions elaborated in the empirical part, the research presented two propositions on how companies should seek to reevaluate their strategies and efficiency indicators and the implementation of Lean Manufacturing practices offer a solid structure to face the organizational challenges inherent to changing the mentality of efficiency in organizations.